Effect of K2so4 Dose and Frequency on Water Content of Red Chilli Varieties (Capsicum Annuum L.) - Muhammad Al qamari (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The Red chili includes perishable foodstuffs such as susceptible to shrinkage due to loss of water, easily decomposed so must be pre-harvest handling techniques and proper post-harvest post-harvest handling. The aim of this research was to evaluate effect of K2SO4 dose and frequency on water content of red chilli varieties. This research was conducted at Experimental field Faculty of Agriculture, UMSU, Medan, from July to November 2016. This research used Split-plot design with two factors. The first factor was red chilli varieties (V) were TM 999 (V1), Lado (V2) and Landung (V3). The second factor was K2SO4 dose and frequency with ten factors were K0 = no K2SO4 (control), dose = 1,5 gr/litre frequency 6 x (K1), 9 x (K2) and 12 x (K3), dose = 3 gr/litre frequency 6 x (K4), 9 x (K5 ) and 12 x (K6), dose = 4,5 gr/litre frequency 6 x (K7), 9 x (K8) and 12 x (K9). The results indicated that K2SO4 Dose and Frewuency showed significant effect on water content of red chilli varieties. Dose and frequency of K2SO4 showed significant effect with control where K9 (4.5 g/litre K2SO4 with 12 times frequency) as the highest during the planting period on all test varieties were TM 999 with 75.77 % water content, Landung, with 77.53% water content, and Lado varieties with 81.64% water content.